Self-reported syphilis and gonorrhoea testing among men who have sex with men: national HIV behavioural surveillance system, 2003–5. Issue 6 (21st November 2008) - Tai, E; Sanchez, T; Lansky, A; Mahle, K; Heffelfinger, J; Workowski, K
Abstract : Objectives: The Centers for Disease Control and Prevention provides guidance on sexually transmitted disease (STD) testing specifically for men who have sex with men (MSM) in STD treatment guidelines to address increasing rates of gonorrhoea and syphilis among MSM in the USA. The guidelines recommend at least annual syphilis, gonorrhoea and chlamydia testing for sexually active MSM. The implementation of these guidelines was evaluated. Methods: Data from the 2003–5 MSM cycle of the National HIV Behavioural Surveillance System were used. The proportion of sexually active HIV-negative MSM reporting syphilis and gonorrhoea testing during the previous year was determined and multivariate logistic regression was used to identify factors associated with testing. Results: Of 10 030 MSM, 39% and 36% reported having been tested for syphilis and gonorrhoea in the previous year, respectively. Four factors were associated with syphilis and gonorrhoea testing, respectively: age 18–24 years versus ⩾45 years (odds ratio (OR) 2.2, 95% CI 1.8 to 2.5; OR 2.7, 95% CI 2.3 to 3.2), black versus white race (OR 1.3, 95% CI 1.1 to 1.4; OR 1.4, 95% CI 1.2 to 1.6), private insurance versus no insurance (OR 1.3, 95% CI 1.1 to 1.4; OR 1.3, 95% CI 1.1 to 1.4) and disclosing male–male sex to a healthcare provider (OR 2.2, 95% CI 2.0 to 2.5; OR 2.1, 95% CI 1.9 to 2.3). Conclusions: Syphilis and gonorrhoea testing among MSM was low, despite specific testing recommendations in the STD treatment guidelines. To increase STD testing among MSM, healthcare providers should assess the risks of STD for male patients through routine enquiries about sexual activity.